Measurement technology and intelligent instruments VIII - Gao, Wei, 1962- (Key engineering materials ;, 2008)
Measurement, rigorously defined as 'ascertaining the size, amount or degree of a measurand by instrumental comparison with a standard unit or by indirect calculation based upon theory', is what makes science and technology different to imagination. Measurement is essential in industry, commerce and daily life. In the manufacturing industry in particular, measurement and instrumentation technology play increasingly important roles not only in the traditional field of manufacturing but also in the new fields of micro/nano technology and bioengineering. This book presents recent advances in the u.